2017
DOI: 10.1016/j.msard.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cognitive impairment among Hungarian patients with relapsing-remitting multiple sclerosis and clinically isolated syndrome

Abstract: Background: Cognitive impairment (CI) is a frequent symptom of multiple sclerosis (MS); its prevalence is reported to be 43-70%. It is one of the most important determinants of MS patients' quality of life, as it is one of the main factors for MS patients becoming unemployed. Aim:We aimed to determine the prevalence of CI among the relapsing-remitting MS (RRMS) and clinically isolated syndrome (CIS) patients in Hungary, to evaluate the predicting factors of CI and to assess the differences between sexes and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 51 publications
3
21
1
1
Order By: Relevance
“…Chiaravalloti & DeLuca, 2008). With more than 300 patients assessed, the sample size made it possible to stratify between sexes, we confirmed our previous and other results regarding the difference of CI's prevalence between men and women (Patti et al, 2015;Sandi et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Chiaravalloti & DeLuca, 2008). With more than 300 patients assessed, the sample size made it possible to stratify between sexes, we confirmed our previous and other results regarding the difference of CI's prevalence between men and women (Patti et al, 2015;Sandi et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of depression (27.0%), fatigue (52.2%), CI (50.9%) in our cohort was in line the literature (Ben Ari Shevil et al, ; Chiaravalloti & DeLuca, ). With more than 300 patients assessed, the sample size made it possible to stratify between sexes, we confirmed our previous and other results regarding the difference of CI's prevalence between men and women (Patti et al, ; Sandi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to various authors, the frequency is in the range of 20 to 45% and is observed even in patients with a clinically isolated syndrome. 7,[11][12][13] According to the study by Achiron and Barak (2003), 95% of the studied patients with possible MS had an abnormal score in at least one neuropsychological test. 14 Cognitive dysfunctions in MS patients have been found to be correlated with a number of other factors besides the type and duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı araştırmacılar bilişsel bozulmanın bazen hastalığın ilk işareti olabileceğini öne sürmekle birlikte 8,38 En az bir testte bozulma saptanan (-1 SD) hasta oranı %64 iken, 2 SD altında kalan hasta oranı %48 olarak saptandı. Literatürde KİS'te bilişsel bozulma prevalansına ilişkin çalışmalarda, %27 ile %57 arasında değişen oranlar bildirilmiştir 51,52 . Achiron ve ark.…”
Section: Uluslararası Multipl Skleroz Yaşam Kalitesi Anketi (Multipleunclassified